Evaluation of LIPI and mGPS as prognostic factors in extensive-stage small-cell lung cancer - Oyman, Abdilkerim; Cil, Ibrahim; Özçelik, Melike; Tataroğlu Özyükseler, Deniz; Başak, Mustafa; Gökyer, Ali; Ökten, İlker Nihat (Journal of Surgery and Medicine, 2022)
Background/Aim: There is an unmet need for effective prognostic models in small cell lung cancer. Lung immune prognostic index (LIPI) and Modified Glasgow Prognostic Score (mGPS) markers are prognostic in various cancers. We aimed to examine LIPI and GPS markers’ prognostic effects on overall survival (OS) in extensive-stage small-cell lung cancer (SCLC) patients. Methods: Patients who were 18 years of age or older, diagnosed with extensive-stage small cell lung carcinoma who received platinum-based chemotherapy as first-line treatment were included in this retrospective observational study. Having concurrent or sequential radiotherapy to the thorax and receiving non-platinum-based chemotherapy as first-line treatment were the criteria for exclusion. We measured their pretreatment LIPI and mGPS markers and performed multivariate Cox regression analyses of progression-free survival (PFS) or OS in extensive stage-SCLC patients. Results: A total of 129 patients were included in the study. Twenty-eight patients (21.7%) were mGPS 0, 65 patients (50.4%) were mGPS 1, and 36 (27.9%) were mGPS 2. Fourteen percent of the patients were LIPI 0 (n=18), %38 were LIPI 1 (n=49), and %48 were LIPI 2 (n=62). The OS of the mGPS 0, mGPS 1, and mGPS 2 patients were 19.0 months (95% CI, 16.3-21.7), 8.4 months (95% CI, 7.1-9.8), and 6.4 months (95% CI, 3.1-9.6) respectively, and those of LIPI 0, LIPI 1, and LIPI 2 patients were 18.3 months (95% CI, 9.9-26.7), 11.7 months (95% CI, 5.3-18.1), and eight months (95% CI, 6.6-9.5), respectively. In the multivariate analysis, ECOG PS 0-1 and LIPI score 0-1 were associated with better PFS (P=0.035 and P=0.03 respectively) and OS (P=0.003 and P=0.036 respectively). Conclusions: LIPI score predicted an unfavorable prognosis, whereas mGPS was not associated with survival. It would be better to consider the use of the LIPI score when managing extensive-stage small cell lung cancer.